(untitled) (Jurnal Intek Akuakultur, 2019)
One of diseases in the white shrimp is white spot disease that caused by White Spot Syndrom Virus (WSSV). Thus, effective effort to prevent WSSV outbreak in shrimp farming is required, and one of which is the administration of immunostimulant. This study aims to examine the effect of feed containing G. verrucosa extract at different doses on the survival of white shrimp infected with WSSV. This study consisted of six treatments of the dose of G. verrucosa and each of three replications, namely KN (without extract), KP (without extract + WSSV infection), A (extract of 2,000 mg / kg + WSSV infection), B (dose of 3,000 mg / kg + WSSV infection), C (4,000 mg / kg + WSSV infection), and D (5,000 mg / kg + WSSV infection). White shrimp with initial body weight of 6-10 g/shrimp were reared in the (60×30×30) cm with density of 10 shrimps/aquarium. Shrimp were given feed (32% protein) containing G. verrucosa extract with a 3% feeding rate of biomass weight three times a day for 14 days. On the 15th day tested challenged with WSSV at a dose of 0.1 mL / intramuscularly. The result showed that feed containing G. verrucosa extract was able to significantly increase the survival of white shrimp compared to the positive control treatment. The best survival after challenge test on treatment C (4,000 mg / kg), which is 56.67 ± 5.74%. It was concluded that the dosage of 4,000 mg / kg of feed gave the best results to improve the survival of white shrimp infected with WSSV.